Multiple Coronary Artery Microfistulas Associated with Apical Hypertrophic Cardiomyopathy: Left and Right Coronary Artery to the Left Ventricle. (11th November 2015) - Choi, Jeong-Woo; Kim, Kyehwan; Kang, Min Gyu; Koh, Jin-Sin; Park, Jeong Rang; Hwang, Jin-Yong
Abstract : A 76-year-old woman underwent coronary angiography for chest pain. On the coronary angiogram, no significant coronary artery atherosclerotic stenosis was observed. Multiple coronary artery microfistulas, draining from the left anterior descending artery to the left ventricle and from the posterior descending artery of the right coronary artery to the left ventricle, were observed. Apical wall thickening and fistula flow from the left anterior descending artery were demonstrated by using transthoracic echocardiography. We describe a rare case of multiple coronary artery microfistulas from the left and right coronary artery to the left ventricle combined with apical hypertrophic cardiomyopathy.